An Experimental Study and Concept Evaluation on Tree-Interior Imaging Radar Using Sinusoidal Template-Based Focusing Algorithm - Betül Yılmaz; Serhat Gökkan; Caner Özdemir (Journal of Electrical and Computer Engineering)
An algorithm for detecting cavities inside a tree-body is presented with simulation and measured examples. The details of the imaging algorithm that is based on sinusoidal template focusing routine are given. First, the algorithm is tested with the simulation scenario for which perfect reconstruction of the simulated cavity structure together with tree-body is successfully formed in MATLAB programming environment. Then, the algorithm is applied to the measurement data that have been collected from a laboratory set-up. Collected backscattered measurements from the tree-body (with cavity) structure are used to generate the image of the scene by the help of our proposed algorithm. The resultant radar images of the measured data collected from the laboratory arrangement have shown the applicability of the developed algorithm for the detection of cavity structures inside tree-bodies.